2014
DOI: 10.1145/2667227
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Field Affects Perceived Depth in Stereographs

Abstract: Although it has been reported that depth of field influences depth perception in nonstereo photographs, it remains unclear how depth of field affects depth perception under stereo viewing conditions. We showed participants stereo photographs with different depths of field using a Wheatstone stereoscope and a commercially available 3D TV. The depicted scene contained a floor, a background, and a measuring probe at different locations. Participants drew a floor plan of the depicted scene to scale. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…us, se ing DoF to the appropriate value enables accurate perception of scale and depth [Held et al 2010;Vishwanath and Blaser 2010] and increases perceived realism [Mauderer et al 2014;Zhang et al 2015].…”
Section: Introductionmentioning
confidence: 99%
“…us, se ing DoF to the appropriate value enables accurate perception of scale and depth [Held et al 2010;Vishwanath and Blaser 2010] and increases perceived realism [Mauderer et al 2014;Zhang et al 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Depth of field, as a pictorial depth cue, is defined as the distance range in which objects are perceived as sharp [ 24 26 ]. Manipulating depth of field is a popular photographical technique that is used widely by photographers and cinematographers to direct viewers’ attention to interesting objects or important parts of a scene [ 27 – 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wang et al [ 15 ] provided evidence that a globally blurred background enhances the perceived depth separation between the background and a sharp, disparity defined foreground object. Nefs [ 8 ] found that depth of field systematically affected perceived depth/width ratio of photographs of natural scenes, while Zhang et al [ 17 ] have shown complex patterns of dependencies between depth of field, height-in-the-field, 3D display system, and perceived depth when observers were asked to draw floor plans of viewed scenes to scale. All these studies find that blur modulates the perception of global scene depth.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from notable exceptions [ 15 17 ], the experiments performed on blur and disparity have generally used impoverished synthetic stimuli, such as lines, gratings and random dot stereograms. These stimuli intentionally avoid monocular cues such as geometric perspective, which are present in everyday viewing of natural scenes.…”
Section: Introductionmentioning
confidence: 99%